2006
DOI: 10.1038/sj.jhh.1002013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of losartan compared with atenolol on the incidence of revascularization in patients with hypertension and electrocardiographic left ventricular hypertrophy. The LIFE study

Abstract: The effect of losartan compared with atenolol on the incidence of revascularization in patients with hypertension and electrocardiographic left ventricular hypertrophy. The LIFE study In the Losartan Intervention For End point reduction in hypertension (LIFE) study losartan-compared to atenolol-based antihypertensive treatment showed a tendency towards reducing peripheral revascularization (4.4 vs 57, P ¼ 0.07). This benefit was significant in the patients without peripheral vascular disease or without albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Of particular note, the antihypertensive strategy most frequently adopted was losartan 100 mg plus hydrochlorothiazide (HCTZ) 12.5 mg and approximately 56% of patients received at least one dose of the combination of losartan 100 mg plus HCTZ 12.5 mg at some time during the study (61). A number of subanalyses of LIFE have also shown that, compared with an atenolol-based regimen, an antihypertensive therapy based on losartan has favourable effects in terms of organ damage protection and CV risk factor correction, as manifested by differential beneficial changes in MAU, LVH, left atrial diameter, AF, brain natriuretic peptide, vascular structure, serum uric acid, new-onset diabetes and lipid metabolism (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Similarly, in patients with diabetes and renal insufficiency, ARBs resulted in greater benefits in improving MAU and slowing progression to end-stage renal disease (ESRD) than comparator drugs (73)(74)(75)(76)(77).…”
Section: Modern Therapeutic Options To Optimally Manage the Hypertensmentioning
confidence: 99%
“…Of particular note, the antihypertensive strategy most frequently adopted was losartan 100 mg plus hydrochlorothiazide (HCTZ) 12.5 mg and approximately 56% of patients received at least one dose of the combination of losartan 100 mg plus HCTZ 12.5 mg at some time during the study (61). A number of subanalyses of LIFE have also shown that, compared with an atenolol-based regimen, an antihypertensive therapy based on losartan has favourable effects in terms of organ damage protection and CV risk factor correction, as manifested by differential beneficial changes in MAU, LVH, left atrial diameter, AF, brain natriuretic peptide, vascular structure, serum uric acid, new-onset diabetes and lipid metabolism (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). Similarly, in patients with diabetes and renal insufficiency, ARBs resulted in greater benefits in improving MAU and slowing progression to end-stage renal disease (ESRD) than comparator drugs (73)(74)(75)(76)(77).…”
Section: Modern Therapeutic Options To Optimally Manage the Hypertensmentioning
confidence: 99%